A new classification of the Arctic spring transition in the middle atmosphere - Matthias, Vivien; Stober, G.; Kozlovsky, Alexander; Lester, M.; Belova, Evgenia; Kero, Johan (2021)
In the middle atmosphere, spanning the stratosphere and mesosphere, spring transition is the time period where the zonal circulation reverses from winter westerly to summer easterly which has a strong impact on the vertical wave propagation influencing the tropospheric and ionospheric variability. The spring transition can be rapid in form of a final sudden stratospheric warming (SSW, mainly dynamically driven) or slow (mainly radiatively driven) but also intermediate stages can occur. In most studies spring transitions are classified either by their timing of occurrence or by their vertical structure. However, all these studies focus exclusively on the stratosphere and can give only tendencies under which pre-winter conditions an early or late spring transition takes place and how it takes place. Here we classify the spring transitions regarding their vertical-temporal development beginning in January and spanning the whole middle atmosphere in the core region of the polar vortex. This leads to five classes where the timing of the SSW in the preceding winter and a downward propagating Northern Annular Mode (NAM) plays a crucial role. The results show distinctive differences between the five classes in the months before the spring transition especially in the mesosphere allowing a certain prediction for some of the five spring transition classes which would not be possible considering the stratosphere only.